A partial revision of the genus Periclimenes Costa, 1884 (Crustacea: Decapoda: Palaemonidae) - Bruce, A. J. (Zootaxa, 2004)
A partial revision of the pontoniine shrimp genus Periclimenes Costa, 1844, is proposed, with the resurrection of the genus Harpilius Dana, 1852, and the designation of a new genus Kemponia. Three species are now placed in the genus Harpilius. Kemponia is designated to include 24 species of an expanded Periclimenes grandis species group . Both genera are primarily coral reef species, with Harpilius species obligatory associates of scleractinian corals. The species of Kemponia are predominantly free-living, some as micro-predators. A few species are associates of scleractinian corals.